2019
DOI: 10.1007/s00122-019-03279-3
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of Rha2 in barley reveals candidate genes for resistance against cereal cyst nematode

Abstract: Key message The cereal cyst nematode resistance locus Rha2 was mapped to a 978 kbp region on the long arm of barley chromosome 2H. Three candidate genes are discussed. Abstract The cereal cyst nematode (CCN) Heterodera avenae is a soil-borne obligate parasite that can cause severe damage to cereals. This research involved fine mapping of Rha2 , a CCN resistance locus on chromosome 2H of bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Barley genome has been sequenced very recently (Mascher et al 2017) and being explored for fine trait mapping. BSA-Seq analysis suggested nine confident genes resulting from fine mapping of the locus Rha2 for cereal cyst nematode (CNN) in barley (Van Gansbeke et al 2019). A seminal paper by Pourkheirandish et al (2015) in barley reported fine mapping of btr1 and btr2 genes to genomic intervals of 1.2 kb and 4.9 kb, respectively, on chromosome 3H by analyzing more than 10,000 F 2 individuals.…”
Section: Model Plants/cropsmentioning
confidence: 99%
“…Barley genome has been sequenced very recently (Mascher et al 2017) and being explored for fine trait mapping. BSA-Seq analysis suggested nine confident genes resulting from fine mapping of the locus Rha2 for cereal cyst nematode (CNN) in barley (Van Gansbeke et al 2019). A seminal paper by Pourkheirandish et al (2015) in barley reported fine mapping of btr1 and btr2 genes to genomic intervals of 1.2 kb and 4.9 kb, respectively, on chromosome 3H by analyzing more than 10,000 F 2 individuals.…”
Section: Model Plants/cropsmentioning
confidence: 99%